Energy‐efficient asset management for professional landlords - Smid, Jan-Willem; Nieboer, Nico (International Journal of Strategic Property Management, 2010)
CO2 reduction by means of energy conservation is an important topic in many governmental environmental policies. As new construction accounts for a fraction of the total building stock, the energy performance of existing dwellings is of great importance. Professional landlords can play a major role in energy conservation, but there are indications that the large energy conservation potential in their housing existing stock is only exploited to a minor extent. This paper presents a method to implement the topic energy conservation in the asset management of professional landlords, in order to establish an integration of energy conservation in their maintenance and renovation practice. This method is described in relation to the asset management of Dutch social housing landlords, but may also be useful for other professional landlords. The method takes advantage of the European EPBD (Energy Performance of Buildings Directive).First published online: 18 Oct 2010